Strategic branding models in Arab media: Exploring the impact of digital transformation - Ilhem Allagui; Mohammed Ibahrine (Communication & Society (Formerly Comunicación y Sociedad))
This study explores the transformative landscape of Arab media branding strategies, focusing on the interplay between technology, diverse ownership models, and strategic innovation. Using Kapferer’s Brand Identity Prism framework, this research examines the branding strategies of 11 prominent Arab media organizations. Findings show that successful Arab media brands combine cultural relevance, visual identity, and advanced digital technologies to build audience trust and loyalty. By leveraging wealth and innovation, Gulf nations promote the creation of technologically advanced media hubs, while other regions prioritize strong connections with local cultural identities. The study identifies four distinct Arab media branding models: the Portals Model, which emphasizes centralized platforms with authoritative voices; the Streamer Model, focusing on high-quality visuals and interactive experiences; the Catalog Model, offering structured content libraries and personalized curation; and the Social Media Model, leveraging real-time communication and emotional engagement to build loyal communities. This study highlights the crucial role of technology in shaping contemporary Arab media branding. It stresses the importance of balancing innovation with cultural and regulatory constraints to maintain long-term competitiveness and relevance in a rapidly changing media environment.